COMPLIANCE MANAGEMENT OF HYPERCHOLESTEROLEMIA IN ELDERY - Musthika Wida Mashitah; Amin Zakaria; Islamia Mei Andista; Hanim Mufarokhah; Rifatul Fani (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2024)
Hypercholesterolemia is an increase in cholesterol levels in the blood. In order for cholesterol levels to remain stable, it is necessary to comply with therapy for the elderly who suffer from hypercholesterolemia. The purpose of this study was to determine the compliance of the elderly regarding the management of hypercholesterolemia in Gunungsari Village, RT 05/RW 02, Tajinan District, Malang Regency. This research was a descriptive research. The population was all elderly (>60 years) totaling 85 people. The sample was 62 people. The sampling technique used accidental sampling with univariate analysis. The research location was in Gunungsari Village, Tajinan District, Malang Regency and the research time was 29 June 2022, questionnaire research instrument. The variable in this study was elderly compliance in the management of hypercholesterolemia. The results of the study of elderly compliance in the management of hypercholesterolemia from 31 respondents lacked adherence, mostly 74% and a minority of 516%. This result was made possible by several factors such as age, gender, marital status, residence of the educator, occupation, drugs consumed, and information received. Based on the results, it is expected to increase compliance and carry out prevention and control by complying with diet, maintaining diet, exercising, quitting smoking, and contributing to family support.